2021
DOI: 10.1080/00071668.2021.1943311
|View full text |Cite
|
Sign up to set email alerts
|

Screening and bioinformatics analysis of cellular proteins interacting with chicken bromodomain-containing protein 2 in DF-1 cells

Abstract: 1. Bromodomain-containing protein 2 (BRD2) is an important member of the BET protein family, which can specifically bind histone acetylated lysine to participate in gene transcriptional regulation, chromatin remodelling, cell proliferation and apoptosis. The following investigation of cellular proteins interacting with chBRD2 will be helpful in understanding the new functions of chBRD2 and the mechanism of NDV replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…BRD2 is reported to interact with many chromatin- and transcriptional activation-related proteins to regulate the transcription of diverse genes [ 32 , 33 , 34 ]. Importantly, several studies have shown that viruses hijacking BRD2 to enhance viral gene transcription is beneficial for viral replication [ 22 , 23 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRD2 is reported to interact with many chromatin- and transcriptional activation-related proteins to regulate the transcription of diverse genes [ 32 , 33 , 34 ]. Importantly, several studies have shown that viruses hijacking BRD2 to enhance viral gene transcription is beneficial for viral replication [ 22 , 23 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al [ 86 ] demonstrated that the M and chicken bromodomain-containing protein 2 (chBRD2) interaction in the nucleus could promote NDV replication. Generally, the BRD2 protein resides within the nucleus and poses significant effects on modulating the gene transcription and host immune responses [ 87 ]. Subsequent research revealed an interaction between both C-terminus domains of the M and chBRD2 proteins.…”
Section: Main Textmentioning
confidence: 99%
“…to promote transcriptional activation of target genes (Rahman, Sowa et al, 2011;Wai, Szyszka et al, 2018). In addition, the ET domain of the BET protein can bind to viral proteins, promoting the integration of the viral genome and host DNA, thereby mediating viral infection and replication (Gallay, Blot et al, 2019;Duan, Han et al, 2020;Aiyer, Swapna et al, 2021;Zhou, Han et al, 2021).…”
Section: Classification and Structure Of Bet Protein Familymentioning
confidence: 99%